Pengaruh Audit Committee, Ownership Structure, dan Chief Executive Officer terhadap Financial Distress pada Perusahaan Sektor Perdagangan, Jasa, dan Investasi yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015-2018 - Maghfiroh, Refiana Dwi; Isbanah, Yuyun (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Financial distress is a condition that occurs before a company goes bankrupt, so before that happens, the company needs to take actions such as good corporate governance practices. The purpose of this research is to determine the effect of the audit committee, ownership structure, and CEO on financial distress in trading, service, and investment companies listed on the Indonesia Stock Exchange for the period 2015-2018. The analysis technique used is logistic regression analysis. This type of research is quantitative by using a sample of 25 companies determined through a purposive sampling technique. The results showed that the frequency of audit committee meetings had a significant and positive impact on financial distress, and institutional ownership had a significant and negative impact on financial distress. While the other variables include: audit committee size, audit committee competence, audit committee independence, managerial ownership, family ownership, government ownership, foreign ownership, block holder ownership, and CEO's gender do not have a significant impact on financial distress. Implications of the results in this study are considering the frequency of audit committee meetings and the percentage of institutional ownership in predicting financial distress that can be used by companies and potential investors.